Multiple photon reactions of organic molecules in solution. - Banks, Jeffrey T. (University of Ottawa (Canada), 1994)
This thesis presents the results from numerous studies on the multiple photon reactions of organic molecules in solution. The initial investigations on the selectivities of radical fragmentation reactions from ground and excited states required the use of both pulsed and continuous wave laser techniques. Laser flash photolysis techniques were used to determine the $\alpha,\alpha$-dimethoxybenzyl radicals undergo fragmentation from the excited state with a quantum yield which is close to one. High intensity laser-jet photolysis was used to determine the selectivities for the excited state fragmentation of unsymmetrically substituted $\alpha,\alpha$-dialkoxybenzyl. It was found that the excited radicals show no selectivity upon fragmentation whereas the ground state radical fragmentations are governed by the thermodynamic stability of the radical products. Lack of a suitable method for the production of semi-preparative amounts of multiple photon reaction products in our own laboratory led us to develop a new technique which utilizes pulsed lasers. By irradiating small droplets of solution with the focused output from a pulse laser we were able to induce multiple photon reactions with efficiencies which are comparable to the laser-jet technique. A direct comparison was made for the case of diphenylmethyl radicals in carbon tetrachloride and methanol. This method, dubbed laser-drop photolysis, was used, along with laser-flash photolysis techniques and conventional lamp irradiations, to investigate and compare the chemistry for several transient species from both the ground and excited states. A number of unique reaction pathways have been found to occur from the excited states of the transient intermediates. For example, ground state 1,1-diphenylethoxyl radicals undergo a neophyl-like rearrangement to yield 1-phenoxy-1-phenylethyl radicals. From the excited state this radical undergoes $\beta$-scission, a process which does not occur from the ground state radical. Irradiation of small drops of liquid by the focused output from high powered pulse lasers results in their destruction in a manner similar to the ablative photodecomposition of organic polymers. We have investigated the dynamics of the drop explosion by taking Polaroid photographs with a time resolution of $\sim$20 ns by using a second pulsed laser as the flash for the camera. The destruction of the drops occurs in the $\mu$s time scale and a model has been proposed which is consistent with the dynamics of drop explosion. Further, pyrene has been used in attempts to probe the temperature increase inside the drop just prior to its explosion.
Keywords: Chemistry, Physical.